2020
DOI: 10.1371/journal.pone.0243532
|View full text |Cite
|
Sign up to set email alerts
|

Captivated by thought: “Sticky” thinking leaves traces of perceptual decoupling in task-evoked pupil size

Abstract: Throughout the day, we may sometimes catch ourselves in patterns of thought that we experience as rigid and difficult to disengage from. Such “sticky” thinking can be highly disruptive to ongoing tasks, and when it turns into rumination constitutes a vulnerability for mental disorders such as depression and anxiety. The main goal of the present study was to explore the stickiness dimension of thought, by investigating how stickiness is reflected in task performance and pupil size. To measure spontaneous though… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 86 publications
2
14
0
Order By: Relevance
“…The observation of task complexity influencing pre-task baselines is consistent with previous studies (e.g., Ganea et al, 2020 ; Irons et al, 2017 ; Mosaly et al, 2017 ; Steiner & Barry, 2011 ) that found similar effects for a broad range of cognitive tasks. Steinhauer and colleagues linked the elevated baselines for difficult tasks with differential preparation and processing ( Steinhauer et al, 2004 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The observation of task complexity influencing pre-task baselines is consistent with previous studies (e.g., Ganea et al, 2020 ; Irons et al, 2017 ; Mosaly et al, 2017 ; Steiner & Barry, 2011 ) that found similar effects for a broad range of cognitive tasks. Steinhauer and colleagues linked the elevated baselines for difficult tasks with differential preparation and processing ( Steinhauer et al, 2004 ).…”
Section: Discussionsupporting
confidence: 91%
“…Second, task complexity might play a role on the relationship between baseline activation and TEPR. Mosaly et al (2017) showed that different relations between baseline and TEPR exist for tasks that have variable loads, such as those measured in, e.g., Kahneman & Beatty (1967) ; Beatty (1982a) , and tasks with sustained challenging conditions (e.g., Gilzenrat et al, 2010 ; Peysakhovich et al, 2017 ). The task considered in the present study of speech understanding in noise is complex and, therefore, it follows that it results in a relation between baseline and TEPR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mind-wandering state has also been linked with a smaller pupil response relative to when the person was on-task (Mittner et al, 2014 ; Unsworth and Robison, 2016 ; Konishi et al, 2017 ). Moreover, we have previously shown that when thoughts are considered to be difficult to disengage from by the participant, they are accompanied by greater reductions in pupil size compared to when they are easier to disengage from (Huijser et al, 2020 ).…”
Section: Introductionmentioning
confidence: 94%
“…These brain oscillations have been found to some what correlated with DMN activation observed in fMRI studies (Mantini et al, 2007 ; Hlinka et al, 2010 ; Jann et al, 2010 ). It is worth noting that there is to our knowledge no data yet on the electrophysiological changes (including the ERPs and brain oscillations) caused by the sticky form of spontaneous thoughts, despite the behavioral and ocular evidence of increased sensory decoupling when the thoughts are more sticky compared to those which are less sticky (Huijser et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%